Women in prison: gender and social control - Zaitzow, Barbara H.; Thomas, Jim (Lynne Rienner Publishers, 2003)
"Women in Prison explores how the gender-based attitudes that women bring to prison frame how they respond to the prison environment - and how gender stereotypes continue to affect the treatment and opportunities of incarcerated women today." "The authors focus especially on how the personal and social problems imported into the prison setting become part of the intricate web of prison culture. Their study reveals just how extensively women's prison experience reflects the control and domination they experienced in the outside world."--BOOK JACKET